Importance of the Congonhas River for the conservation of the fish fauna of the Upper Paraná basin, Brazil - DIEGO AZEVEDO ZOCCAL GARCIA; ANA PAULA VIDOTTO-MAGNONI; ALEXANDRO DERLY AUGUSTO COSTA; ARMANDO CÉSAR RODRIGUES CASIMIRO; LUCAS RIBEIRO JARDULI; JOÃO DANIEL FERRAZ; FERNANDA SIMÕES DE ALMEIDA; MÁRIO LUÍS ORSI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Garcia DAZ, Vidotto-Magnoni AP, Costa ADA, Casimiro ACR, Jarduli LR, Ferraz JD, De Almeida FS, Orsi ML. 2019. Importance of the Congonhas River for the conservation of the fish fauna of the Upper Paraná basin, Brazil. Biodiversitas 20: 474-481. The Upper Paraná River basin is among the most fragmented watersheds in the world. The Congonhas River belongs to this drainage system, which has its mouth in the Capivara Reservoir and can be considered the largest tributary free-from-dam, becoming important for the maintenance of fish species richness. In order to know more about the species present in this tributary, we aimed to provide an inventory of fish fauna of the Congonhas River and reproductive strategies to determine whether the river is used by migratory species and whether there is a longitudinal variation in the fish assembly. These findings will provide subsidies to contribute to the implementation of policies to protect biodiversity. Samplings occurred in the upper, middle and lower stretches of the Congonhas River during four periods between 1991 and 2011. Fishes were captured using gill nets from 2 to 14 cm mesh sizes between opposite knots and cast nets, identified and categorized according to their reproductive strategies. A total of 4,640 individuals belonging to 63 species, of which 79.4% consisted of Characiformes and Siluriformes were captured. Furthermore, 14% of fish were long-distance migratory species (e.g., Piaractus mesopotamicus, Megaleporinus obtusidens, Prochilodus lineatus, Salminus brasiliensis, Pinirampus pirinampu, and Pseudoplatystoma corruscans). In addition, there was an increase in the fish species richness from upstream to downstream. Management actions such as prohibition of fishing, rehabilitation of riparian vegetation, and protection of the basin against dam construction will reduce anthropogenic impacts on the ecosystem. The Congonhas River highlights the importance of preserving lotic environmental for the conservation of migratory and non-migratory Neotropical fish diversity into a heavily modified watershed.